The “High Inspection” in education: An unknown service of the Spanish educational system - Álvarez-Álvarez, Carmen; Rodríguez-Bravo, Marcos Francisco; Camacho-Prats, Alexandre (Education Policy Analysis Archives, 2019)
Inspection in schools is carried out by the educational inspection service dependent on the autonomous communities, which have full powers in terms of control, supervision, advice and evaluation. However, the different laws of education that have governed our educational system, include the existence of a “High Inspection” in education, a service dependent on the Ministry of Education, Culture and Sport and whose competences are explicit in our current educational law. In this article we synthesized an exploratory study on the current situation of the high inspection in Spain through interviews with key informants, whose purpose is to know the access procedure to perform the functions entrusted to the high inspection, their real skills and their coordination with the autonomous educational inspection. The results show that the control competences of this service are reduced, in addition to checking that its functions are limited to inform the Ministry about elements of the autonomic regulations that may contravene the basic regulations, the decision making about the homologation and issuance of titles, in addition to other state competences not transferred. We conclude that the high inspection is a service that develops many functions related to information or verification, which currently, with some exceptions, are not exercising those personal inspector positions and that is an unknown service for many, besides having a name that generates confusion.